A balanced digital diet for under 5s: A commentary on Orben (2021). Issue 3 (11th January 2022) - Bidgood, Amy; Taylor, Gemma; Kolak, Joanna; Bent, Eve Marie; Hickman, Nicola
Abstract: Orben (2021) proposed a 'Digital Diet' approach to thinking about children's consumption of digital media. Here, we consider the Digital Diet with a focus on young children under 5. As well as discussing how Type and Amount apply to this age group, we argue that Balance needs to be considered differently for young children, and their families, compared to older children and adolescents. Considering the developmental needs of preschool children, we suggest that Balance must include not only a balance of activities within the digital world, but beyond it. The Digital Diet should be part of a wider healthy lifestyle, involving a range of activities and, crucially, social interaction. We also suggest an additional dietary factor: Timing of digital media use. Supporting children to form healthy Digital Diet habits early in life, may enable them to maintain a healthy digital lifestyle themselves as they continue to grow.